2004
DOI: 10.1016/j.jpainsymman.2003.10.013
|View full text |Cite
|
Sign up to set email alerts
|

The association between nocturnal hot flashes and sleep in breast cancer survivors

Abstract: This study examined the relationship between objectively measured nocturnal hot flashes and objectively measured sleep in breast cancer survivors with insomnia. Twenty-four women who had completed treatment for non-metastatic breast cancer participated. All were enrolled in a study of cognitive-behavioral treatment for chronic insomnia. Nocturnal hot flashes and sleep were measured by skin conductance and polysomnography, respectively. The 10-minute periods around hot flashes were found to have significantly m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
2
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(87 citation statements)
references
References 37 publications
4
77
2
4
Order By: Relevance
“…However, participants in the current study reported longer sleep duration than reported in prior work with breast cancer patients [10,11]. This is not surprising since research in the general population suggests women in their fifties experience more nocturnal disturbances [16], possibly due to hot flashes [3]. The second aim was to identify factors related to sleep.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…However, participants in the current study reported longer sleep duration than reported in prior work with breast cancer patients [10,11]. This is not surprising since research in the general population suggests women in their fifties experience more nocturnal disturbances [16], possibly due to hot flashes [3]. The second aim was to identify factors related to sleep.…”
Section: Discussionmentioning
confidence: 47%
“…Previous research suggests rates of insomnia, one type of sleep disorder, may be three times higher among patients receiving chemotherapy than the general population [1]. Sleep disturbances may be related to pain [2], hot flashes [3], or psychological factors [2]. Sleep disturbances affect patients with a variety of cancer diagnoses, can persist through treatment and survivorship, and are associated with greater depression and fatigue [1,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most typical menopausal distresses are hot flushes and sweating, interfering with activities, sleep and HRQoL [7][8][9]. Hot flushes are more common, severe and longlasting in women with breast cancer than in healthy women [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…. Sans aller jusqu'à ces situations extrêmes, il a été montré que les troubles du sommeil sont plus fréquents chez les femmes après cancer du sein qu'après d'autres types de cancer et sont significativement associés avec la présence de BdC nocturnes [6,7].…”
Section: Généralitésunclassified